Impact of Biodex systems equipment in prevention of ankle joint instability in junior footballers - Xhardo, Kristo; Cordun, Mariana; Gherghel, Carmen Liliana; Stănescu, Rares; Onita, Cristiana; Corciova, Calin; Onu, Ilie; Pandea, Alin; Iordan, Daniel Andrei; Iacob, George Sebastian; Minculescu, Cozeta Anca; Cristuta, Mihaela Alina; et al. (Balneo and PRM Research Journal (Online. English ed.), 2023)
Background: The aim of this study was to identify differences in impact in the prevention of second-degree ankle sprain recurrence, more precisely agonist-antagonist muscle rebalance, recovery of proprioception junior footballers will have a different impact on patients undergoing rehabilitation program with the help of Biodex 4 Pro and Biodex balance compared to those who perform physical therapy using classical exercise programs. (2) Methods: the study included 30 subjects divided into two equal groups according to the agreement to practice modern exercise programs and soccer-specific exercises: the experimental group which performed exercises through Biodex 4 pro and biodex balance and the control group which performed classical exercises. Part evaluations included: Biodex balance for a range of stability assessments and the PodoSmart device for running assessment. (3) Results: Analyzing the data of the present scientific research, it can be concluded that the athletes belonging to experimental group 1, for which the intervention was carried out using modern means, did not register any recurrence at the level of the ankle, compared to the athletes included in the experimental group 2 for which the intervention was carried out with the help of classic means of recovery and which recorded an average of 1.46 recurrences (sprains) at the level of the ankle.(4) Conclusion: The study has shown that the Biodex System 4 Pro and Biodex Balance (together with the other modern therapies mentioned in the current paper) are very helpful in the recovery process.